Dios y Ser: Una aproximación desde Eckhart y Heidegger - Castañeda Vargas, José (2023)
This paper attempts to examine the possible relationships that can be drawn between the experiences of God in Meister Eckhart, of being in Martin Heidegger, and Reality in Zen Buddhism, drawing parallels, suggesting meeting points and indicating differences or aspects that differ in their understanding and the sense of the three experiences. It is based on the explanation of what Eckhart understands as God, then attempts to understand what being refers to in Heidegger and concludes with the basic concepts of Zen Buddhism, attempting to weave together three concepts which are so original in their approaches, and conserving for each their identity and difference.